Comparing FAST and BEFAST in Acute Stroke Patients: A Systematic Review - Iqbal, Muhammad; Rizal, Muhammad (The Indonesian Journal of General Medicine, 2024)
Background: Stroke leads to cerebral infarct, and time increases risk of infarct progression to healthy tissue. Further insult and secondary neuronal injury (such as hypoxia) can accelerate the progression of the infarct. The only definitive management strategies for ischaemic stroke are reperfusion and endovascular thrombectomy. Methods: This systematic review focused on full-text English literature published between 2014 and 2024 using the PRISMA 2020 guidelines. Editorials and review pieces published in the same journal as the submission without a DOI were not accepted. The literature was compiled using Medline, Science Direct, Scopus and Embase, among other online venues. Result: Five publications were found to be directly related to our ongoing systematic examination after a rigorous three-level screening approach. Subsequently, a comprehensive analysis of the complete text was conducted, and additional scrutiny was given to these articles. Conclusion: FAST is a useful screening tool for identifying stroke at call-taker level. FAST has acceptable sensitivity when used as a screening tool; however, specificity and diagnostic effectiveness are lacking.